The Accelerating Land Carbon Sink of the 2000s May Not Be Driven Predominantly by the Warming Hiatus - Zaichun Zhu; Shilong Piao; Tao Yan; Philippe Ciais; Ana Bastos; Xuanze Zhang; Zhaoqi Wang (Geophysical Research Letters)
Abstract Recent studies attributed the accelerating land carbon sink (SLAND) during the 2000s to respiration decrease induced by the warming hiatus. We used two long‐term atmospheric inversions, three temperature data sets, and eight ecosystem models to test this attribution. Our results show that the changes in seasonal SLAND trend between the warming (1982–1998) and hiatus (1998–2014) periods do not track evidently the changes in seasonal temperature trends at both global and regional scales. A conceptual model of the annual/seasonal temperature response of respiration suggests that changes in seasonal temperature during this period are unlikely to cause a significant decrease in annual respiration. The ecosystem models suggest that trends in both gross primary production and terrestrial ecosystem respiration slowed down slightly, but the resulting slight acceleration in net ecosystem productivity is insufficient to explain the increasing trend in SLAND. Instead, the roles of alternative drivers on the accelerating SLAND seem to be important.